2013
DOI: 10.1016/j.jcol.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological and clinical features of familial adenomatous polyposis in Ribeirão Preto

Abstract: Purpose to study 75 familial adenomatous polyposis (FAP) patients treated in a single institution in Ribeirão Preto/SP, from January 1981 to December 2011. Methods this is a retrospective study and the following data were collected: gender, age, main symptoms, familial history, coexisting malignancies, surgical treatment, surgical morbidity and mortality, factors related to life quality. Results median age was 29 years. Male-to-female ratio was 1.2:1. Bleeding was the most common symptom (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Tumor-associated antigens and autoantibodies have generated increasing interest as biomarkers for the development of innovative diagnostic and prognostic tools that have an effective role in the management of human cancers. 26 Feitosa et al 27 concluded that genetic counseling and proper screening programs are essential tools for the early diagnosis and follow-up of cases of CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor-associated antigens and autoantibodies have generated increasing interest as biomarkers for the development of innovative diagnostic and prognostic tools that have an effective role in the management of human cancers. 26 Feitosa et al 27 concluded that genetic counseling and proper screening programs are essential tools for the early diagnosis and follow-up of cases of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical features of patients with colorectal adenocarcinoma (colorrectal cancer group: patients 1-25; control group: patients[26][27][28][29][30][31][32][33][34][35] …”
mentioning
confidence: 99%
“…Familial adenomatous polyposis (FAP) is a part of genetic polyposis syndrome which is caused by germline mutation in the adenomatous polyposis coli (APC) gene located in chromosome 5q21. 1 The incidence is estimated at one in every 8,000-10,000 live births and accounts for less than 1% of cases of colon cancer. 2,3 The frequency is constant throughout the world, with men and women equally affected.…”
Section: Introductionmentioning
confidence: 99%
“…Colonic meanwhile the extraintestinal manifestationinclude congenital hyperthrophy of retinal epithelium, epidermoid cyst, desmoid tumor, and pancreatic cancer. 1,3 Patients tend to develop hundreds to thousand adenomatous polyp between the second and third decades of life. 1 If left untreated, almost 100% patients will develop colorectal cancer by the age 50 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation